Enhanced Extraction of Silicon-Vacancy Centers Light Emission Using Bottom-Up Engineered Polycrystalline Diamond Photonic Crystal Slabs - Ondič, Lukáš; Varga, Marian; Hruška, Karel; Fait, Jan; Kapusta, Peter (ACS nano, 2017)
Silicon vacancy (SiV) centers are optically active defects in diamond. The SiV centers, in contrast to nitrogen vacancy (NV) centers, possess narrow and efficient luminescence spectrum (centered at ≈738 nm) even at room temperature, which can be utilized for quantum photonics and sensing applications. However, most of light generated in diamond is trapped in the material due to the phenomenon of total internal reflection. In order to overcome this issue, we have prepared two-dimensional photonic crystal slabs from polycrystalline diamond thin layers with high density of SiV centers employing bottom-up growth on quartz templates. We have shown that the spectral overlap between the narrow light emission of the SiV centers and the leaky modes extracting the emission into almost vertical direction (where it can be easily detected) can be obtained by controlling the deposition time. More than 14-fold extraction enhancement of the SiV centers photoluminescence was achieved compared to an uncorrugated sample. Computer simulation confirmed that the extraction enhancement originates from the efficient light-matter interaction between light emitted from the SiV centers and the photonic crystal slab.
Keywords: leaky modes; polycrystalline diamond; photonic crystal slab; photoluminescence; silicon-vacancy center